Experimental phase diagram of negatively supercoiled DNA measured by magnetic tweezers and fluorescence. Issue 7 (23rd January 2015) - Vlijm, Rifka; Mashaghi, Alireza; Bernard, Stéphanie; Modesti, Mauro; Dekker, Cees
Abstract : Phase diagram of experimentally determined DNA structures under (extreme) negative supercoiling. Abstract : The most common form of DNA is the well-known B-structure of double-helix DNA. Many processes in the cell, however, exert force and torque, inducing structural changes to the DNA that are vital to biological function. Virtually all DNA in cells is in a state of negative supercoiling, with a DNA structure that is complex. Using magnetic tweezers combined with fluorescence imaging, we here study DNA structure as a function of negative supercoiling at the single-molecule level. We classify DNA phases based on DNA length as a function of supercoiling, down to a very high negative supercoiling density σ of −2.5, and forces up to 4.5 pN. We characterize plectonemes using fluorescence imaging. DNA bubbles are visualized by the binding of fluorescently labelled RPA, a eukaryotic single-strand-binding protein. The presence of Z-DNA, a left-handed form of DNA, is probed by the binding of Zα77, the minimal binding domain of a Z-DNA-binding protein. Without supercoiling, DNA is in the relaxed B-form. Upon going toward negative supercoiling, plectonemic B-DNA is being formed below 0.6 pN. At higher forces and supercoiling densities down to about −1.9, a mixed state occurs with plectonemes, multiple bubbles and left-handed L-DNA. Around σ = −1.9, a buckling transition occurs after which the DNA end-to-end length linearly decreases when applying more negative turns, into a state that we interpret as plectonemic L-DNA. By measuring DNA length, Zα77 binding, plectoneme and ssDNA visualisation, we thus have mapped the co-existence of many DNA structures and experimentally determined the DNA phase diagram at (extreme) negative supercoiling.